Comparação entre a competitividade do Brasil e Canadá para a produção de madeira serrada - Almeida, Alexandre Nascimento de (2013)
The survival of business in a scenario of accelerated globalization and increase competition depends on its degree of competitiveness of the business and the market. In this aspect the comparison among the worlds best standards is fundamental to the improvement of industry practices and procedures for the production of softwood lumber. Canada is an excellent example and parameter to use as a comparison in the softwood lumber industry with Brazils industry. The aim of this study was to compare competive softwood lumber markets between Brazil and Canada using the concepts of performance and efficiency. For this purpose the methodologies used were: constant market share, index of revealed comparative advantage, regression analysis and chi-square test to subsidize the viewpoint of performance. These have been applied to factor analysis, Cluster analysis and the Mann-Whitney test to assess the competitiveness of efficiency. The basis of the analysis for both concepts uses secondary and primary data that reflect current historical terms. The results indicate that Canada is more competitive than Brazil in the softwood lumber industry, however Brazil has better performance bringing together its industry in the face of world adversities.